Change of root and rhizosphere characters of willow (Salix sp) induced by high heavy metal pollution - Máthé-Gáspár, Gabriella (Acta Biologica Szegediensis, 2006)
The abandoned Pb/Zn mine causes heavy metal problems in the surrounding area at Gyöngyösoroszi (North-Hungary). The Toka-river transported heavy metal (Cd, Cu, Pb, Zn) ions from several heaps deposited imprudently near a historic lead and zinc-mining site. Willow (Salix sp.) is one of the plants often applied for phytoremediation practice, since its high metal accumulation capacity. Proposal of this work was to investigate the change of root and rhizosphere characters of willow plants induced by high heavy metal pollution. The response of root mass/soil samples, fine root mass/other roots and BAF-s (bioaccumulation factors) and also two soil biological properties soil microbial biomass and acid phosphatase activity to heavy metal pollution were studied. All measured biological parameters have proved to indicate soil pollution, root mass decreased, portion of fine root increased, BAF-s values with exception of Cd decreased significantly. Both measured biological parameters of willow rhizosphere therefore could indicate soil pollution, but change was adverse, biomass decreased while phosphatase activity increased. Microbial biomass and phosphatase activity were not correlated, indicating different account of ecological factors that altering biological properties of a soil.